The multifaceted lexis of Kerstner’s Gruntovčani - Josip Lasić; Željka Macan; Marina Marinković (Studia Lexicographica, 2023)
A particular community is, among other things, also determined by its speech (Pon 2009), and the most conspicuous indicator of the distinctiveness of a given speech, as well as an important linguistic means of national integration and differentiation, is its lexis (Pranjković 2007, 488). The lexis of certain Croatian speeches was shaped by many external influences, namely through the »entry« of lexemes from other, mostly neighbouring languages and linguistic systems (Lisac 2003, 31). This paper analyses the lexis of the cult Croatian TV series Gruntovčani, created by Mladen Kerstner, based on the scripts of the first five episodes: Božja vola (The Will of God Will), Jelen (Deer), Babica su nakanili hmreti (Granny Has Decided to Die), Zlatna jajca (Golden Eggs), and Ovce idu (There Go the Sheep). The speech in question belongs to Kajkavian, primarily the author’s native speech of Ludbreg, interspersed with numerous foreign dialectal elements. The aim of this study is to present the multifaceted nature of the lexis in the TV series Gruntovčani, which is analysed from several perspectives: dialectological, sociocultural, and semantic-pragmatic. The main focus is on the three lexical layers of Kerstner’s text: inherited Slavic lexical layer, loanwords, and internationalisms. The three main findings are as follows: 1. lexemes of Slavic origin greatly correspond to those from Chakavian and Shtokavian as well as Slovenian, and a large number of neologisms and words characteristic of Kajkavian are also observed; 2. there are many loanwords, especially Germanisms; 3. internationalisms, words that have entered Kajkavian primarily due to social and political circumstances of the time, are observed in smaller measure. All of this suggests that the lexis of Gruntovčani is multifaceted, just like today’s local speeches, and that the sources used indicate the desire for language, as a television medium and in accordance with the time and place of the plot, to faithfully and authentically represent reality.